Effect of degree of ripening on the quality of virgin olive oils produced in Longnan, China. (9th September 2021) - Lü, Xiaofei; Ma, Junyi; Yan, Huiqiang; Yang, Lihua; Ren, Xiaoxia; Guo, Junwei; Yong, Qiaoning; Kong, Weibao; Deng, Yu
Abstract: The main purpose of this work was to study the effect of different ripening degree (0–7) on quality of two monovarietal olive oils (Arbequina and Arbosana) produced in Longnan region, located in the northwest of China, Gansu province. The qualitative characteristics of oils are evaluated by analysis of the principal quality parameters and chemical composition, such as: free acidity, peroxide value, K232, K270, oxidative stability, fatty acid composition, total phenols, flavonoids content and flavor profile. The maximum oil yields were obtained for both varieties at a ripening degree of 7 (13.26% and 23.59%). The Arbequina and Arbosana oils contained oleic acid (ranged 53.16%–58.92% and 66.30%–74.30%, respectively) and linoleic acid (ranged 15.51%–18.77% and 7.25%–9.45%), respectively. The ratio of MUFA/PUFA ranged from 2.93 to 3.77 and 6.73 to 9.84, respectively. The ratio of 18:1/18:2 presented ranges of 2.84–3.79 and 7.02–9.94, respectively. A significant relationship was observed between the total polyphenols (83.48–140.53 and 118.32–230.00 mg GAE⋅kg −1 ), flavonoids (0.43–9.00 and 10.20–5.51 mg RE⋅kg −1 ) and the oxidative stability. E–Nose could effectively identify and distinguish between different varieties and ripening degree of olive oil, especially that change in the W1W (sulfur‐organic) sensor. A principal component analysis showed that the particular effect of ripening degree in the cultivars olive oils.